Internationalization of traditional Chinese medicine: current international market, internationalization challenges and prospective suggestions - Annie Xianghong Lin; Ging Chan; Yuanjia Hu; Defang Ouyang; Carolina Oi Lam Ung; Luwen Shi; Hao Hu (BMC, 2018)
Abstract Through reviewing the current international market for traditional Chinese medicine (TCM), this paper identified the internationalization challenges for TCM, including unclear therapeutic material basis and mechanism, difficulty of quality control, low preparation level, registration/policy barriers, and shortage of intellectual property. To deal with these challenges, suggestions were given including: (1) product innovation of TCM (study the TCM by using the methods and means of western medicine; innovate the basic theory of TCM; develop TCM health product); (2) standard innovation of TCM; (3) building big data platform of Chinese medicine (big data platform of TCM preparation; big data platform on the quality of TCM).